신경문합술과 피브린접합술 후 활동전위차 및 신경재생 효과 - 정태영(Tae-Young Jung); 김욱규(Uk-Kyu Kim); 정인교(In-Kyo Chung); 신상훈(Sang-Hoon Shin) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2005)
The purpose of this study was to compare clinical availability of fibrin adhesive technique with microneural suture technique. We applicated fibrin adhesive technique and microneural suture technique on cut sciatic nerve in rat and used to Compound muscle action potential of rat thigh muscle compartment and histologic finding for comparision of clinical availability. The results were as following. 1. Using latency and amplitude in Compound muscle action potential test, we compared microneural suture technique with fibrin adhesive technique for nerve regeneration effect. the means was slightly different between two method. but there’s no statistically significant differences. 2. Histologic finding was similar in microneural suture technique and fibrin adhesive technique for regeneration of axon and myelin sheath in destruction site after nerve anastomosis. These results showed that the efficacy of fibrin adhesive technique was similar to that of conventional microneural suture technique. Moreover, fibrin adhesive technique is decreased operating time and imporved of incapability of accessment in conventional suture technique. Therefore this technique is a useful method to nerve anastomosis in nerve enervation and neurotransplantation. KCI Citation Count: 0